KNOWLEDGE AND AWARENESS OF ORAL CONTRACEPTIVE PILLS AND THEIR SOCIO-DEMOGRAPHIC DETERMINANTS AMONG WOMEN OF REPRODUCTIVE AGE IN SOUTH PUNJAB, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Background: One of the most common family planning methods that are mostly used to date is oral contraceptive pills, which however, require knowledge and awareness amongst the women in order to be used effectively. The socio-cultural limitations, women education, and inaccessibility of healthcare facilities in Pakistan, especially in South Punjab, might influence the women’s understanding of oral contraceptives, which might result in misuse and persistent misconceptions.Objective: This study aimed to determine the level of knowledge and awareness of women of South Punjab, Pakistan regarding oral contraceptive pills and to assess the socio-demographic and healthcare access-related factors associated with these outcomes.Methods: A community-based cross sectional study was designed. For this, 750 women aged between 18-49 years were selected using multi-stage stratified sampling technique. The data was collected from the women of three districts of South Punjab, Pakistan including Multan, Bahawalpur, and Dera Ghazi Khan by employing the interviewer-administered structured questionnaire consisting of socio-demographic variables and knowledge-related aspects of oral contraceptives usage. The SPSS version 25 was used to carry out descriptive statistics, chi-square tests, Kruskal-Wallis tests, and multivariate logistic regression analyses.Results: It was found in this study that majority of the respondents were aware of basic knowledge like daily use and intake of contraceptive pills, and reduced effectiveness when these pills are missed. Moreover, significant knowledge gaps and uncertainty were recorded in this study regarding protection against sexually transmitted infections (STIs), the requirement of perceptions, using oral contraceptives while breastfeeding, and proper usage practices. Better knowledge and awareness of oral contraceptives were significantly associated with higher education, urban settings, and the proximity to healthcare facilities.Conclusion: The research revealed fragmented knowledge and inadequate understanding of oral contraceptive pills amongst South Punjab women. The education interventions and access to reproductive health education, especially in the rural regions are necessary to promote informed and effective contraceptive use.